Laboratory objective method for noise reduction measurements of ear-muffs - Emil KOZŁOWSKI; Ewa KOTARBIŃSKA (Archives of Acoustics)
The aim of the project was to work out a laboratory method for measurements of noise reduction of ear-muffs whose results are in better agreement with real-world performance than the results of sound attenuation measurements according to PN-EN 24869-1. The paper presents the methodology for noise reduction measurements of ear-muffs with the use of a four-channel sound analyzer. The laboratory test site met the requirements of PN-EN 24869-1. The objective tests were carried on with sixteen persons. The microphones were placed at the subject's ear under the ear-muffs' cups and outside the cups. The measurements were carried on four samples of ten models of ear-muffs. The comparison of noise reduction measurements data with the sound attenuation measured according to PN-EN 24869-1 is discussed.